Field Observations Reveal How Plunging Mixing and Sediment Resuspension Affect the Pathway of a Dense River Inflow Into a Deep Stratified Lake - Koen Blanckaert; Love Råman Vinnå; Damien Bouffard; Ulrich Lemmin; David Andrew Barry (Water Resources Research)
Abstract The pathway of dense river inflows into lakes, which affects the lake water quality, is not accurately predicted by existing models. The pathway of a dense riverine inflow in a lake with a submerged canyon is analyzed based on measurements during a 4‐month period of weakening lake stratification and weakening density excess between river and epilimnion. In line with models, the dense riverine inflow plunges upon entering the lake, continues as an underflow on the sloping lake bottom, and finally intrudes at its level of neutral buoyancy. Underflow and interflow velocities are O(0.1 m s−1). The river inflow is finally trapped in the pycnocline most of the time, even when the river's density excess and the lake's stratification are marginal. This trapping in the pycnocline is explained by the reduction of the inflow density excess due to the intense plunging mixing, which is an order of magnitude larger than that obtained in confined laboratory flumes. The pathway of the dense riverine inflow is affected by interactions of the underflow with the lake bottom and sedimentary processes. A canyon carved by the underflows confines and accelerates the underflow, which enhances its capacity to entrain and carry sediment. The entrainment of sediment that was previously deposited on the canyon bottom accelerates the underflow. Due to both effects, the underflow can temporarily break through the pycnocline and reach the hypolimnion. Existing models explain these observations qualitatively, but a quantitative prediction would require better parameterizations of the plunging mixing and the sedimentary processes.